The Variability of Paleoproductivity Proxies in Nearshore East Coast Peninsular Malaysia During Holocene - Sharif, Hamad Maalim; Minhat, Fatin Izzati; Yunus, Kamaruzzaman; Naim, Erick; Shaari, Hasrizal (Marine Science Department Diponegoro University, 2025)
The Holocene epoch was marked by significant climatic fluctuations that shaped marine productivity across tropical coasts. This study reconstructs Holocene paleoproductivity along the East Coast of Peninsular Malaysia, specifically Terengganu (TER16-GC13C) and Kelantan waters (KELC17) using core sediments. A multi-proxy approach was applied, analysing biogenic silica (BSi), total organic carbon (TOC), calcium carbonate (CaCO₃), and elemental ratios (Ca/Al, Ca/Fe, Ba/Al) to evaluate changes in productivity in response to sea-level and monsoonal variability. Results indicate distinct temporal patterns: the early Holocene showed elevated BSi and TOC linked to enhanced nutrient influx during rapid sea-level rise. While the mid-Holocene exhibited reduced carbonate deposition due to strong terrigenous input associated with the East Asian Summer Monsoon and the late Holocene was marked by increased CaCO₃ deposition reflecting reduced riverine input and greater biogenic production during sea-level highstand decline. Elemental ratios corroborate these shifts, highlighting the dynamic interplay between terrigenous and marine sources.These findings demonstrate that sea-level change was a dominant driver of productivity variations, modulated by monsoonal strength. The strong correlation between terrigenous proxies and grain size underlines the role of hydrodynamics in sediment delivery. This study contributes an integrated Holocene paleoproductivity reconstruction for East Coast Peninsular Malaysia, providing a regional baseline that complements South China Sea records. The results enhance understanding of tropical shelf ecosystem sensitivity to climate variability, offering a reference framework for assessing future climate change impacts on coastal productivity.